Development of a core outcome set for studies on prevention and management of pregnancy-associated venous thromboembolism (COSPVenTE): a study protocol - Rohan D’Souza; Alexandria King; Lizabeth Teshler; Nadine Shehata; Ann K Malinowski (BMJ Open)
Introduction Pregnancy and post partum are times of heightened risk for the development of venous thromboembolism (VTE), which in turn is one of the leading causes of maternal mortality and long-term morbidity. The current research aimed at improving health guidelines for women with pregnancy-associated VTE is limited by inconsistency in outcome reporting preventing comparison across studies, and lack of input from patients with respect to outcomes they propose are most important to measure. A suggested solution is the development of a core outcome set (COS) that defines the minimum criteria for outcome reporting in clinical trials and prospective studies. COSs function to facilitate data harmonisation and increase homogeneity in outcome reporting while incorporating the voice of women in this population in the planning of research to inform their ongoing care.Methods and analysis The development of a COS for studies on pregnancy-associated VTE will comprise five steps. First, a systematic review of the published literature will identify currently reported outcomes, their definitions and measurements if applicable. This will be followed by in-person interviews with patients, clinicians, researchers, hospital administrators and policy-makers to identify outcomes they consider important. Third, the long list of outcomes obtained from steps I and II will be condensed through online Delphi surveys involving an international group of relevant stakeholders including patients. This will be followed by a face-to-face consensus meeting with representatives of all stakeholder groups to arrive at a consensus on the final COS. Lastly, to determine how the identified core outcomes should be measured, another literature review and Delphi process will be carried out as necessary.Ethics and dissemination This study has been approved by the Mount Sinai Hospital Research Ethics Board (REB 18-0314-E). Study results will be published in open-access journals and presented at obstetrics, maternal–fetal medicine and haematology conferences. All progress will be documented on the international prospective register of systematic reviews (PROSPERO) and Core Outcome Measures in Effectiveness Trials databases.PROSPERO registration number CRD42019111479.